(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to produce student worksheets for system of linear equation three variables (SPLTV) based on problem solving that valid and practical and has potential effects for students. The method consists of five stages: analysis, design, development, implementation, evaluation. The data collection techniques used in this research are questionnaire, test and interview. The subject of study were student in 7 Palembang State Senior High School. Based on the research results obtained a set of valid, practical and has a potential effects for students worksheets based on problem solving in the topic system of linear equation three variables. The validity of student worksheets the can be seen from three aspects, namely content, construct and language carried out at the expert review stage as well as comments and suggestions from the results of the one-to-one trial. The practicality of student worksheets can be seen from the calculation results of the practicality questionnaire given at the small group stage. The student worksheets presented some problem based on problem solving and it can help students practice numeration skills in mathematics learning in the topic system of linear equation three variables.